Adolescentes em medidas sócio-educativas: saúde mental, auto-estima, suporte social e estilos parentais - Silva, Maria Denise Pessoa (Universidade Federal de São Carlos, 2009)
According to researchers, adolescence has been considered a risk age group for various mental health problems, such as: depression, behavioral problems and substance abuse. However, only a few Brazilian studies investigate mental health problems among young offenders, although the international literature agrees on the fact that juvenile offenders suffer from various mental health problems. Besides mental health, studies indicate that self-esteem, social support and parenting can also affect adolescents behavior and development. The aim of the present study was to identify the profile of male young offenders in treatment and also to identify correlations between levels of mental health, self-esteem, social support and parenting and correlations between these elements and other profile variables, such as age, education levels, substance abuse, among others. Another objective was to identify the adolescents perception of themselves, their difficulties and positive characteristics, their help resources and plans for their future. Fifty adolescents took part in the study. They answered a semi-structured interview and completed the following instruments: Identification Questionnnaire; Young Offenders Profile; Rosenberg Self-Esteem Scale, Social Support Appraisals, Parenting Inventory and Strengths and Difficulties Questionnaire. The scores were calculated according to each instrument. The Pearson Correlation Coefficient was used to identify possible correlations between the scores of these instruments and the Pearson Correlation Coefficient was used to verify possible correlations between the scores of the instruments and the adolescents profile variables. The interview analysis has been carried out through the Content Analysis. The main results indicated that most of the adolescents have low education levels and use marijuana, besides having friends who also use drugs. High selfesteem levels could be observed in this sample. Besides, it was possible to verify that levels of education, social support from teachers and positive parenting might be protection factors against vulnerable behavior, once it was possible to identify negative correlation between social support from teachers and use of cocaine and negative correlations between positive monitoring and recidivism and alcohol abuse, which indicates that the more the adolescents parents perform positive parenting, the lower the recidivism and alcohol abuse levels. We expect that this study can contribute to the planning and implementation of public actions aiming the treatment of young offenders.
Young Offenders: mental health, self-esteem, social support and parenting
Keywords: Adolescentes; Infratores; Saúde mental; Autoestima; Suporte social; Estilos parentais; Adolescentes em conflito com a lei; Young offenders; Mental health; Self-esteem; Social support; Parenting; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL